2010
DOI: 10.1111/j.1468-1331.2010.03279.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and personality features in patients with lateralized Parkinson’s disease

Abstract: This study suggests that side dominance of dopaminergic denervation may be related to personality features in patients with PD that could influence behavioral aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
(62 reference statements)
2
11
0
Order By: Relevance
“…The relevance of this laterality is corroborated by further observations: first, by the higher predominance of right-sided symptoms in PD, compared to leftsided ones [12]. And secondly, as several non-motor symptoms including cognitive decline [13], hypomania [14] or anosognosia [15] have a distinct prevalence depending upon the side in which PD-symptoms manifest first. Probably, this reflects distinct affection of the two hemispheres.…”
supporting
confidence: 54%
“…The relevance of this laterality is corroborated by further observations: first, by the higher predominance of right-sided symptoms in PD, compared to leftsided ones [12]. And secondly, as several non-motor symptoms including cognitive decline [13], hypomania [14] or anosognosia [15] have a distinct prevalence depending upon the side in which PD-symptoms manifest first. Probably, this reflects distinct affection of the two hemispheres.…”
supporting
confidence: 54%
“…For statistical analysis we also used the Asymmetry subscale of the UPDRS, which indicates the degree of right-versus left-sided motor severity. The decision to use UPDRS asymmetry scores as a proxy for right/left forebrain dysfunction is supported by several reports that demonstrate neurobehavioral differences in rightversus left-onset PD patients (Katzen, Levin, & Weiner, 2006;Piacentini, Versaci, Romito, Ferre, & Albanese, 2011;Tomer & Aharon-Peretz, 2004;Tomer, AharonPeretz, & Tsitrinbaum, 2007;Tomer, Levin, & Weiner, 1993). Specifically, left-onset PD patients are allegedly more vulnerable to change in personality features, executive, and frontostriatal dysfunction.…”
Section: Neuropsychological Examination and Disease Severitymentioning
confidence: 93%
“…A study [9] adopting the 16 Personality Factors [48] reported that PD patients tested as more socially alert, tense, apprehensive, driven, self-reproaching, cautious, restless and sceptical compared to HC. Two studies [49,50] adopted the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) [51]. In the first study [49] PD patients reported higher scores than HC on Depression, Hysteria, Hypochondriasis and Social Introversion, and in the second study [50] left-lateralized PD patients had higher score in the Hypomania scale relative to right-lateralized PD patients.…”
Section: Other Personality Models and Parkinson's Diseasementioning
confidence: 99%
“…Two studies [49,50] adopted the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) [51]. In the first study [49] PD patients reported higher scores than HC on Depression, Hysteria, Hypochondriasis and Social Introversion, and in the second study [50] left-lateralized PD patients had higher score in the Hypomania scale relative to right-lateralized PD patients. A study [51] adopting the Brooks & McKinlay Personality Inventory [52] reported that PD patients tested as less talkative and flexible and more cautious, generous and even-tempered compared to HC.…”
Section: Other Personality Models and Parkinson's Diseasementioning
confidence: 99%